Patologia seksualna w systemie rodzinnym - Beisert, Maria (Wydawnictwo Naukowe UAM, 2005)
The article proposes an analysis of the family as a system which, when faced with the threatt of a breakup, is capable of resorting to pathological mechanisms in order to ensure durability and continuity. The article is an attempt to answering the question of how and for what reasons it is possible that a family can overstep the norm, and why it should continue to maintain the pathology despite the conquences it may face.
Referat wygłoszony podczas XII Ogólnopolskiego Zjazdu Socjologicznego w Poznaniu w ramach grupy ad hoc „Profesor Zbigniew Tyszka jako główny badacz rodziny w ostatnim ćwierćwieczu XX wieku”